Menses, fertility and pregnancy following the use of balloon tamponade technology in the management of postpartum haemorrhage. (8th February 2014) - Georgiou, Christos
<x xml:space="preserve">Abstract</x> This manuscript describes five cases of pregnancies and births in women that have previously required the uterine‐specific Bakri™ balloon in the management of postpartum haemorrhage. In addition, this manuscript reviews the impact on menses, fertility and subsequent pregnancies as potential surrogate effects on the myometrium and endometrium, when balloon tamponade technology is used as a 'uterine‐sparing' second‐line approach in the management of postpartum haemorrhage.